Meta-Analysis the Effect of Oral and Injection Contraceptives on Breast Cancer - Rahardjo, Setyo Sri; Pamungkasari, Eti Poncorini; Dilma’aarij, Dilma’aarij (Journal of Maternal and Child Health, 2021)
Background: Oral contraceptives and injec